[PP.30.12] BIOAVAILABILITY AND BENEFICIAL EFFECTS OF OMEGA-3-PUFA-ENRICHED CHICKEN-MEAT: A PILOT STUDY. (September 2016) - Brennan, M.; Allen, S.; Buskandar, F.; Shortall, K.; Hayes, H.; Williams, D.; Moran, N.; Stanton, A.
Abstract : Objective: Greater consumption of oily fish, and elevated plasma levels of the long-chain marine-derived omega-3 polyunsaturated fatty acids (omega-3-PUFAs), have been strongly and consistently associated with reduced incidences of heart attacks, strokes, cognitive decline and cancers. Despite international guidelines recommending 2 servings per week of oily fish (>250 mg/day omega-3-PUFAs), many people do not eat fish at all, and therefore worldwide, deficiencies are common. Omega-3-PUFAs supplements have not consistently provided the same beneficial protection – possible explanations include differences in bioavailability, poor adherence, and/or too late commencement of supplements. In this project, we studied a recently developed alternative to oily fish or supplementation, namely chicken-meat naturally enriched with algae-sourced omega-3-PUFAs. The primary objective was to test if regular consumption of omega-3-PUFA-enriched chicken-meat resulted in measurably higher plasma levels of omega-3-PUFAs. Design and method: In an open sequential study in 30 healthy participants, blood and urine sampling, BP and heart rate measurements, occurred at baseline, and after 1, 3 and 5 weeks of eating 3 servings/week of omega-3-PUFA-enriched chicken-meat. Results: Plasma omega-3-PUFAs levels increased from 82 μg/g at baseline to 93 μg/g at five weeks (12% increment, p = 0.006, Figure). Also at 5 weeks, clinic systolic BP reduced from 116 to 113 mmHg (p = 0.014), and urinary thromboxane (measure of platelet turnover) reduced from 1435 to 1024 pg/mg creatinine (p = 0.037). Figure. No caption available. Conclusions: This study suggests that regular consumption of omega-3-PUFA-enriched chicken-meat increases plasma omega-3-PUFA levels, and that this increase is paralleled by improved cardiovascular health biomarkers. As levels appeared to be continuing to rise at 5 weeks, further increments in plasma levels of omega-3-PUFAs, and greater heart, brain and cancer benefits may be achieved with more prolonged eating of omega-3 enriched chicken-meat. Omega-3-PUFA-enriched chicken-meat may offer an attractive alternative to eating oily fish or taking supplements for many consumers.